Challenges of protecting electronic works in the era of artificial intelligence: a legal and doctrinal perspective - Albnian, Ahmad; Alghathian, Ghazi; Allouzi, Adel (Frontiers in Human Dynamics, 2025)
This study examines the legal deficiencies in protecting artificial intelligence (AI)-generated educational content within Jordan’s rapidly digitizing environment. Jordan’s intellectual property laws lack explicit provisions addressing non-human authorship, algorithmic reproduction, and derivative generation, creating doctrinal ambiguities and enforcement challenges. Using a doctrinal–comparative methodology, the research analyzes Jordanian legislation, international treaties, and the WIPO AI-IP framework, with comparative benchmarks drawn from France, Egypt, the United Arab Emirates, the United States, and the United Kingdom. Secondary data, including IP enforcement statistics, cybercrime assessments, and a SWOT analysis of the Digital Inclusion Strategy, were incorporated to validate and contextualize the findings. The results reveal three major gaps: ambiguity in AI authorship and attribution, procedural underperformance in enforcement mechanisms, and limited cross-border legal cooperation. To address these challenges, the study proposes a tripartite reform framework encompassing statutory recognition of AI authorship, blockchain-based attribution protocols, and regional evidence-sharing mechanisms. These recommendations aim to modernize Jordan’s digital intellectual property governance and provide scalable insights for other Global South jurisdictions confronting similar legal and technological transformations.